New strategy of web-based mental health intervention for psychological distress among working housewives during Covid-19 pandemic in Indonesia: a review - Rusadi, Cici Permata; Wahab, Abdul; Asma, Syifa Nurul (BKM Public Health and Community Medicine, 2021)
Objective: This paper aims to describe the use of web-based mental health services (telepsychology) that can reduce anxiety symptoms, improve positive emotions and sleep quality during the Covid-19 outbreak for working housewives.Content: In Indonesia, the dual role of mothers as workers and housewives during the Covid-19 pandemic increases stress so that it has an impact on the treatment of mothers towards their children and is associated with strict parenting in the form of punishment so that children are at risk of experiencing cognitive and motor development disorders and psychopathology in children. In terms of overcoming anxiety and psychological pressure experienced by housewives, targeted an early intervention strategy is needed to prevent the long-term impact of the COVID-19 pandemic on the mental health of mothers and families. Mental health interventions based on positive psychology principles that include elements of cognitive-behavioral therapy and behavioral activation therapy aim to reduce symptoms of anxiety and depression and improve positive emotions and sleep quality during the Covid-19 outbreak through the telepsychology system. Effectiveness of web-based interventions for cognitive behavioral therapy and therapy for therapist-guided and non-therapist-guided acceptance and commitment tested in case and control groups by comparing the results of the Patient Health Questionaire-9 (PHQ-9) measurement scale and the General Anxiety Disorder-7 scale (GAD-7) showed that GAD-7 scores in the intervention group had a significant reduction (β = -3.27; 95% CI: -5.71, -0.83) with R2 0.106. PHQ-9 score was significantly reduced in the intervention group (β = -4.311; 95% CI: -7.33, -1.29) with R2 0.173. There is a growing body of literature showing the effectiveness of online therapy on the psychological impact of COVID-19. In fact, having therapist support makes a substantial difference in the effectiveness of online interventions especially for working housewives.